Factors associated with adverse nutritional status of children in sub‐Saharan Africa: Evidence from the Demographic and Health Surveys from 31 countries - Sulaimon T. Adedokun; Sanni Yaya (Wiley, 2021)
Abstract Undernutrition is linked to almost half of all deaths in under‐five children. In 2019, 144 million under‐five children suffered from stunting and 47 million suffered from wasting. This study examined the factors that influence adverse nutritional status of children in sub‐Saharan Africa. The study used data from the Demographic and Health Surveys (DHS) of 31 countries, which involved 189,195 children under age 5. Binary logistic regression was used to examine the relationships between the independent variables and adverse nutritional status of children. About 26% of the children in the 31 countries in sub‐Saharan Africa considered in this study are stunted, 6% are wasted and 21% are underweight. Close to 31% of children whose mothers have no education are stunted, 9% are wasted and 28% are underweight. Adverse nutritional status of children is significantly associated with maternal age, education, household wealth, residence, antenatal care attendance, mass media exposure, child's sex and size of child at birth. This study has shown that adverse nutritional status of children is a major challenge in sub‐Saharan Africa. Efforts at improving nutritional status of children should include poverty alleviation initiatives at individual and household levels, increase in women's educational level and improvement in living conditions in rural areas.